Who Is an Evangelical?: The History of a Movement in Crisis - Kidd, Thomas S. (Yale University Press, 2019)
A leading historian of evangelicalism offers a concise history of evangelicals and how they became who they are today Evangelicalism is arguably America’s most controversial religious movement. Nonevangelical people who follow the news may have a variety of impressions about what “evangelical” means. But one certain association they make with evangelicals is white Republicans. Many may recall that 81 percent of self†‘described white evangelicals voted for Donald Trump, and they may well wonder at the seeming hypocrisy of doing so. In this illuminating book, Thomas Kidd draws on his expertise in American religious history to retrace the arc of this spiritual movement, illustrating just how historically peculiar that political and ethnic definition (white Republican) of evangelicals is. He examines distortions in the public understanding of evangelicals, and shows how a group of “Republican insider evangelicals” aided the politicization of the movement. This book will be a must†‘read for those trying to better understand the shifting religious and political landscape of America today